Clinical results of active scanning proton therapy for primary liver tumors. Issue 1 (February 2021) - Dionisi, Francesco; Brolese, Alberto; Siniscalchi, Benedetta; Giacomelli, Irene; Fracchiolla, Francesco; Righetto, Roberto; Morganti, Alessio G.; Pravadelli, Cecilia; Avancini, Ivo; Rozzanigo, Umberto; Mattiuzzi, Angela; Frisinghelli, Michela; et al.
Background: Evidence for the efficacy of radiation therapy for primary liver cancer is growing. In this context, proton therapy (PT) can potentially improve the therapeutic ratio, as demonstrated by recent clinical studies. Here we report the first European clinical experience on the use of PT for primary liver cancer. Methods: All patients treated for primary liver cancer in our center entered the analysis. Patients were simulated during deep expiration breath-hold. A 15-fraction treatment schedule was adopted using active scanning PT. Clinical outcome and toxicity were retrospectively analyzed. Results: Between January 2018 and December 2019, 18 patients were treated. Fourteen patients had hepatocellular carcinoma (HCC), three patients had intrahepatic cholangiocarcinoma (ICC), and one patient had synchronous ICC-HCC. The Child-Pugh score was A5 in the majority of patients with HCC (71.4%). Median prescription dose was 58.05 Gy (range, 50.31–67.5). Median follow-up was 10 months (range, 1–19). The majority of deaths occurred from liver tumor progression. One-year overall survival (OS) was 63%. A significant correlation between worse OS and patient performance status, vascular invasion, and tumor stage was recorded. One-year local control was 90%. Toxicity was low, with a decrease in Child-Pugh score ⩾2 points detected in one patient. No cases of classic radiation-induced liver disease occurred. Conclusions: Our initial results of active scanning PT for primary liver cancer demonstrated the feasibility, safety, and effectiveness of this advanced technique in this setting. The potential of the combination of PT with other locoregional therapies is under evaluation.